Goracy lod - Roberts, Nora.; Zbikowska, Malgorzata (Warszawa : Swiat Ksiazki, 2003)
Polish translation of "Hot Ice". Whitney MacAllister returns to New York after a stay in Paris. There are jewel thieves about who may or may not be apprehended.
Translation of: Hot ice.
Keywords: Thieves -- Fiction; Jewelry theft -- Fiction; Manhattan (New York, N.Y.) -- Fiction; Madagascar -- Fiction